STUDENTS’ PERCEPTION ON TEACHERS’ TEACHING STRATEGIES IN TEACHINGREADING SKILL - Chairunnisya Hamzah; Elsje Sambouw, Irmawaty Umar (Adisam Publisher, 2025)
The purpose of this research was to investigate the students’ perception on teachers’ teaching strategies in teaching reading skill. A qualitative descriptive method was used in this research. In order to answer the research question, the researcher collected data from questionnaire. the researcher distributed a questionnaire to the students that contained some questions in order to get perception on the teacher's strategies in teaching reading. Data analysis in this research used descriptive analysis and the process used is tabulating data, which includes scoring and tabulating. The results of the research on student perception towards teaching strategies in teaching reading indicated that the most preferred strategies are brainstorming, predicting, and making connections. On the other hand, students did not recommend the use of visualizing, summarizing, and questioning as effective reading strategies. This research also suggest that teachers/lecturers should consider incorporating more brainstorming, predicting, and making connections activities in their reading instruction to better engage to their students.